Progressive multifocal leukoencephalopathy outcomes in patients with multiple sclerosis treated with dimethyl fumarate. Issue 4 (October 2022) - Lyons, Jennifer; Hughes, Richard; McCarthy, Kerry; Everage, Nicholas; Kapadia, Shivani; Miller, Catherine; Singhal, Priya; Smirnakis, Karen
Background and objectives: Dimethyl fumarate (DMF), an oral disease-modifying therapy with an established benefit and well-described safety profile, is among the most commonly used therapies for relapsing forms of multiple sclerosis. As of 31 December 2021, >560, 000 patients have been treated with DMF, representing >1, 190, 000 person-years of exposure. Of these, 6413 patients (14, 292 person-years) were from clinical trials. Methods and results: Progressive multifocal leukoencephalopathy (PML) has occurred in the setting of lymphopenia (<0.91 × 10 9 /L) in patients treated with DMF. We present detailed clinical characteristics and outcomes of the 12 confirmed PML cases occurring in MS patients on DMF as of 21 July 2021. The PML incidence in DMF-treated patients is 1.07 per 100, 000 person-years of DMF exposure. Lymphopenia is the common risk for PML in DMF treatment. Discussion: DMF-related PML is rare but has occurred in the setting of lymphopenia, supporting the current recommendations for absolute lymphocyte count monitoring in all patients, regardless of age and time on therapy.